Proceedings of the 7th ACM SIGCOMM Conference on Internet Measurement 2007
DOI: 10.1145/1298306.1298341
|View full text |Cite
|
Sign up to set email alerts
|

Quality-of-service class specific traffic matrices in ip/mpls networks

Abstract: In this paper we consider the problem of determining traffic matrices for end-to-end demands in an IP/MPLS network that supports multiple quality of service (QoS) classes. More precisely, we want to determine the set of traffic matrices T i for each QoS class i separately. T i contains average bandwidth levels for QoS class i for every pair of routers within the network. We propose a new method for obtaining QoS class specific traffic matrices that combines estimation and measurement methods: We take advantage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…We then scale the inter-arrival times to match the values in the traffic data. Additionally, we used a distribution of source-destination flows from a real internet service provider [54] to map flows to different ToS classes. Our dataset includes 4 real-world network topologies, including one previously used (GEANT) and three new topologies that the model has never seen before (ABILENE, NOBEL-GBN, and GERMANY50).…”
Section: B Generalization and Scalabilitymentioning
confidence: 99%
“…We then scale the inter-arrival times to match the values in the traffic data. Additionally, we used a distribution of source-destination flows from a real internet service provider [54] to map flows to different ToS classes. Our dataset includes 4 real-world network topologies, including one previously used (GEANT) and three new topologies that the model has never seen before (ABILENE, NOBEL-GBN, and GERMANY50).…”
Section: B Generalization and Scalabilitymentioning
confidence: 99%
“…Then, we scale these inter-arrivals according to the values in the traffic matrices. Regarding the mapping of sourcedestination flows to ToS classes, we follow the same distribution from a real ISP [58].…”
Section: Experiments With Real Trafficmentioning
confidence: 99%
“…Finally, we evaluate TwinNet using a dataset that combines the 106 real network topologies previously used (Section 7.4), and with traffic matrices that follow the inter-arrivals times and ToS classes mentioned used in the previous experiment [57,58]. Fig.…”
Section: Experiments With Real Trafficmentioning
confidence: 99%
“…To ensure a smooth change of the ability vector, it is necessary to adjust the time interval, during which the traffic matrix can be considered as unchanged. Previous studies have shown that the time interval is from 5 to 15 minutes [12].…”
Section: Qos-aware Dynamic Map Selection While Retaining the Balance ...mentioning
confidence: 99%